Single Nucleotide Polymorphisms in the Human Leukocyte Antigen Region Are Associated With Hemagglutination Inhibition Antibody Response to Influenza Vaccine - Zhong, Shuyi; Wei, Hejiang; Li, Mao; Cheng, Yanhui; Wen, Simin; Wang, Dayan; Shu, Yuelong (Frontiers in Genetics, 2022)
Background: The annual death associated with seasonal influenza is 290,000–650,000 globally, which can be effectively reduced by influenza vaccination. However, the protective hemagglutination inhibition (HAI) antibody response to influenza vaccine is affected by many factors, among which single nucleotide polymorphisms (SNPs) in the human leukocyte antigen (HLA) region can alter the antigen-presenting function of the HLA molecule, thus influencing the process of antibody mounting against vaccine antigen. Methods: Healthy subjects of the Han nationality were recruited and received seasonal trivalent influenza vaccine. Paired serum samples collected on and approximately 28 days after vaccination were tested in parallel by HAI assays. HLA alleles related to the immune response to influenza vaccine reported in the previous literature were summarized, and six corresponding tag SNPs were selected and genotyped using the MassARRAY technology platform. Results: The effects of HLA SNPs on HAI antibody response to influenza vaccine varied with different vaccine antigens. The AA genotype of rs41547618 was correlated with low A/H1N1-specific antibody titer compared with the GG + GA genotype (p = .007). The TT genotype of rs17885382 was correlated with low A/H3N2-specific antibody titer compared with the CC + CT genotype (p = .003). In addition, haplotype consisting of rs41542812—rs17885382—rs2068205—rs41547618—rs6905837—rs9270299—CCTGCA was correlated with non-responsiveness to influenza vaccine (OR = 2.39, 95% CI = 1.02–5.62). Conclusion: HLA SNPs were associated with HAI antibody response to influenza vaccine, which can help in a better understanding of the varied responsiveness to influenza vaccine in the population.